Swellings of the Palate: A Review - Srishti Chatterjee (Institute of Medico-legal Publications Pvt Ltd, 2020)
The palate which forms the roof of the mouth can be divided anatomically into hard and soft palates. Theseareas are actively involved with feeding and speech. The posterior part of the hard palate consisting of theminor salivary glands is a common site for palatal swellings. However, these are quite challenging for theclinician to diagnose and because of the importance of the oral cavity in terms of both function and cosmetics,management of such swellings requires a thorough understanding of the lesion and its progression. Thisarticle reviews the various palatal swellings in terms of their etiologies, clinical features, diagnosis, andmanagement.